Monoclonal antibody for phosphorylated TRIO Y2681 that helps predict prognosis of post-operative colorectal cancer patients - Taro Aoyama; Fumihiko Kakizaki; Hiroyuki Miyoshi; Masahiro Sonoshita; Hisatsugu Maekawa; Yoshiro Itatani; Kenji Kawada; Ryo Matsusue; Iwao Ikai; Koki Moriyoshi; Takaki Sakurai; Kazutaka Obama; et al. (BJC Reports)
Abstract Background We previously reported that TRIO pY2681, a novel prognostic biomarker for CRC, can be detected by polyclonal antibodies (pAb). We have now developed a novel monoclonal antibody (mAb) that recognizes TRIO pY2681. This study aims to assess the utility of immunohistochemical (IHC) staining using the TRIO pY2681 mAb as a prognostic marker for CRC in clinical practice. Methods IHC using TRIO pY2681 mAb was performed on surgical specimens from 357 CRC patients at Kyoto Medical Center and 320 at Kyoto University Hospital. Based on the results, we conducted a retrospective outcome analysis. Results TRIO pY2681 mAb exhibited significantly higher titers than pAb. In both cohorts of all stages, TRIO pY2681 IHC positivity correlated with shorter disease-specific survival (DSS) (HR, 1.67; 95% CI, 1.00–2.79; P = 0.046, and HR, 5.84; 95% CI, 2.26–15.1; P < 0.001) and relapse-free survival (RFS) (HR, 1.92; 95% CI, 1.15–3.22; P = 0.011, and HR, 4.36; 95% CI, 2.17–8.76; P < 0.001). The trend persisted in stage III. Multivariate analysis confirmed TRIO pY2681 IHC positivity as an independent prognostic factor for RFS. Conclusions The novel TRIO pY2681 mAb identifies CRC patient subsets with poorer prognoses, enhancing prognostic precision in clinical settings.